Muon flux measurement at China Jinping Underground Laboratory - Guo, Zi-yi; Bathe-Peters, Lars; Chen, Shao-min; Chouaki, Mourad; Dou, Wei; Guo, Lei; Hussain, Ghulam; Li, Jin-jing; Liu, Qian; Luo, Guang; Luo, Wen-tai; Qi, Ming; et al. (Chinese physics C, 2021)
China Jinping Underground Laboratory (CJPL) is ideal for studying solar, geo-, and supernova neutrinos. A precise measurement of the cosmic-ray background is essential in proceeding with R&D research for these MeV-scale neutrino experiments. Using a 1-ton prototype detector for the Jinping Neutrino Experiment (JNE), we detected 264 high-energy muon events from a 645.2-day dataset from the first phase of CJPL (CJPL-I), reconstructed their directions, and measured the cosmic-ray muon flux to be cm s . The observed angular distributions indicate the leakage of cosmic-ray muon background and agree with simulation data accounting for Jinping mountain's terrain. A survey of muon fluxes at different laboratory locations, considering both those situated under mountains and those down mine shafts, indicates that the flux at the former is generally a factor of larger than at the latter, with the same vertical overburden. This study provides a convenient back-of-the-envelope estimation for the muon flux of an underground experiment.